Resin composition and molded article
By designing continuous and dispersed phase structures in the resin composition and improving the compatibility of PBAT and PLA using acryloyl copolymers, the problem of increasing viscosity of the resin composition when improving compatibility and mechanical properties is solved, achieving the goal of achieving Excellent processability and biodegradability.
Patent Information
- Application Number
- CN202380042394.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-05-25
- Filing Date
- 2023-04-12
- Publication Date
- 2025-01-03
AI Technical Summary
The existing biodegradable resin compositions are difficult to control the increase in viscosity while improving compatibility and mechanical properties, limiting their processability and application expansion.
By introducing the structure of continuous and dispersed phases into the resin composition, the melt flow ratio measured by ISO 1133 and the number and size of the dispersed phase regions observed by transmission electron microscopy are adjusted, and the melt index and number of dispersed phase regions are combined with acryloyls The copolymer acts as a chemical compatibilizer to improve the compatibility of PBAT and PLA.
The mechanical properties of the resin composition are improved and viscosity control are controlled, and its excellent processability and biodegradability are ensured, and it is suitable for the production of molded products.
Smart Images

Figure CN119256048A_ABST
Abstract
Description
[Technical field]
[0004] The present invention relates to a resin composition and a biodegradable molded product molded therefrom. Background Art
[0005] Thermoplastic resins have excellent mechanical properties and chemical characteristics and are therefore used in various fields such as drinking water containers, medical applications, food packaging, food containers, automotive molded products, and agricultural vinyl resins.
[0006] Among them, polyethylene film is mainly used as heat-sealed bags for food packaging or agricultural mulch films, etc., because the polyethylene film has excellent mechanical properties and is non-toxic to the human body and can be continuously deformed when heated.
[0007] Heat-seal bags for food packaging are widely used for vacuum packaging of food and the like, and polyethylene films capable of achieving excellent adhesive strength even at low sealing temperatures are mainly used for heat-seal bags for food packaging.
[0008] Agricultural mulch is commonly used in mulch farming. Mulch is a material that covers the surface of the soil when planting crops. When the upper surface of the soil is covered with various types of materials, weeds can be prevented from growing, pests can be prevented, and the use of pesticides can be reduced. In addition, the temperature of the soil can be easily controlled, beneficial bacteria can be cultivated in the soil, soil erosion can be prevented, and soil moisture can be retained. Examples of covering materials can include rice straw, leaves of crops such as grass, or polyolefin films, and synthetic resins such as polyethylene films are usually mainly used.
[0009] However, polyethylene films do not decompose in the natural environment and also have limitations in recycling. In particular, recently, plastics such as discarded polyethylene films are thrown into the ocean and broken into very tiny microplastics due to backflow and sunlight in the ocean, and this phenomenon is a new problem. It is known that countless such microplastics exceeding billions to tens of billions float in the ocean, enter the bodies of marine organisms, accumulate in the ecosystem, and affect the entire food chain.
[0010] Therefore, interest in biodegradable plastics has increased recently. Among biodegradable plastics, polybutylene adipate terephthalate (hereinafter referred to as PBAT) and polylactic acid (hereinafter referred to as PLA) have attracted attention as biodegradable plastics, and efforts have been continuously made to improve the compatibility of PBAT and PLA in a biodegradable resin composition containing both PBAT and PLA.
[0011] The compatibilizer for the biodegradable resin composition containing PBAT and PLA can be divided into physical compatibilizer and chemical compatibilizer according to the operating principle. As physical compatibilizer, it is representative to use the compatibilizer of the copolymer containing PBAT or PLA. However, when using this physical compatibilizer, since the physical compatibilizer plays an effect similar to that of plasticizer, the disadvantage is that the mechanical properties are deteriorated.
[0012] Chemical compatibilizers use compounds containing functional groups that can react with both ends of the polymer and act as chain extenders, thereby showing the characteristics of increasing molecular weight. However, the disadvantage is that when the overreaction of the functional groups occurs, the viscosity of the resin composition increases rapidly, resulting in difficulty in processing. Therefore, conventional chemical compatibilizers are usually used in resin compositions in very limited amounts.
[0013] Meanwhile, patent registration number 10-2045863 (patent document 1) discloses a biodegradable polyester film comprising an epoxy group and containing a copolymer using styrene, acrylate and / or methacrylate as a base material. When the copolymer disclosed in patent document 1 is used as a compatibilizer for PBAT and PLA, the copolymer used in a specific amount or more causes the following disadvantages: not only PBAT-g-PLA is formed at the interface between PBAT and PLA, but also PBAT-g-PBAT and / or PLA-g-PLA are formed in large quantities in each resin, thus causing the viscosity of the resin composition to increase rapidly. Due to the rapid increase in viscosity that is difficult to control during the processing of the resin composition, the expansion of the application of the resin composition is limited. Therefore, it is important to ensure that the compatibilizer maintains the performance as a chemical compatibilizer in the biodegradable resin composition comprising a heterogeneous biodegradable resin, while being able to ensure processability by controlling the increase in viscosity within an appropriate range.
[0014] Prior art literature
[0015] [Patent document]
[0016] (Patent Document 1) KR 10-2045863B1 Summary of the invention
[0017] Technical issues
[0018] The present invention is made to solve the problems of the prior art and provides a biodegradable resin composition comprising heterogeneous biodegradable resins, wherein the melt index and the number of regions of a dispersed phase are adjusted by improving the compatibility between the heterogeneous biodegradable resins, thereby preventing viscosity increase while improving mechanical properties.
[0019] That is, an object of the present invention is to provide a biodegradable resin composition comprising a heterogeneous biodegradable resin, in which the melt index and the number of regions of a dispersed phase are adjusted by improved compatibility, so that the resin composition has excellent processability by preventing viscosity increase while having improved mechanical properties.
[0020] Furthermore, another object of the present invention is to provide a molded article which is molded from the resin composition and exhibits biodegradability.
[0021] Technical Solution
[0022] To solve the above limitations, the present invention provides a resin composition and a molded article.
[0023] (1) The present invention provides a resin composition comprising a continuous phase and a dispersed phase, wherein the continuous phase comprises a first biodegradable resin, the dispersed phase comprises a second biodegradable resin, a melt flow ratio measured at 190° C. with a load of 5 kg according to ISO 1133 is 3.0 g / 10 min to 13.5 g / 10 min, and when an image obtained by performing image capture at a magnification of 25,000 times using a transmission electron microscope (TEM) is observed, the number of domains of the dispersed phase is 35 or more.
[0024] (2) In the above (1) of the present invention, there is provided a resin composition wherein the first biodegradable resin comprises an aliphatic polyester unit and an aromatic polyester unit.
[0025] (3) In any one of the above (1) or (2) of the present invention, there is provided a resin composition, wherein the first biodegradable resin comprises polybutylene adipate terephthalate.
[0026] (4) In any one of the above (1) to (3) of the present invention, there is provided a resin composition wherein the second biodegradable resin comprises polylactic acid.
[0027] (5) In any one of the above (1) to (4) of the present invention, a resin composition is provided, wherein, relative to 100 parts by weight of the total of the first biodegradable resin and the second biodegradable resin, the content of the first biodegradable resin is 50 parts by weight to 90 parts by weight, and the content of the second biodegradable resin is 10 parts by weight to 50 parts by weight.
[0028] (6) In any one of the above (1) to (5) of the present invention, a resin composition is provided, wherein the melt flow ratio of the resin composition measured at 190° C. with a load of 5 kg according to ISO1133 is 4.5 g / 10 min to 12.0 g / 10 min.
[0029] (7) In any one of the above (1) to (6) of the present invention, a resin composition is provided, wherein the domain size of the dispersed phase observed in an image obtained by image capture at a magnification of 25,000 times using a transmission electron microscope (TEM) is 700 nm or less.
[0030] (8) In any one of the above (1) to (7) of the present invention, a resin composition is provided, wherein the melting enthalpy (ΔHm) is 0.01 J / g to 3.6 J / g, and the melting enthalpy is measured using a differential scanning calorimeter (DSC) in the following manner: adding 8 mg (error range is 1 mg) of a sample, heating once to 180°C at a heating rate of 10°C / min under a nitrogen flow, then cooling to -50°C at a cooling rate of 10°C / min, and heating a second time to 180°C at a heating rate of 10°C / min.
[0031] (9) In any one of the above (1) to (8) of the present invention, there is provided the resin composition, wherein the weight average molecular weight of the entire resin composition is 137,000 to 200,000.
[0032] (10) In any one of the above (1) to (9) of the present invention, there is provided the resin composition, wherein the tensile strength of the resin composition measured at a tensile speed of 50 mm / min according to ASTM D638 is 245 kgf / cm 2 Up to 500kgf / cm 2 .
[0033] (11) In any one of the above (1) to (10) of the present invention, there is provided the resin composition further comprising at least one of an acrylic copolymer and a compatibilizing portion derived from the acrylic copolymer.
[0034] (12) In the above (1) to (11) of the present invention, the resin composition is provided, wherein the acryl-based copolymer may contain a methyl (meth)acrylate monomer unit, a (meth)acrylate monomer unit containing an epoxy group, and an alkyl (meth)acrylate monomer unit having 2 to 10 carbon atoms.
[0035] (13) In any one of the above (1) to (12) of the present invention, a resin composition is provided, wherein the acryl copolymer contains 25% to 65% by weight of the methyl (meth)acrylate monomer unit, 15% to 60% by weight of the (meth)acrylate monomer unit containing an epoxy group, and 5% to 32% by weight of the alkyl (meth)acrylate monomer unit having 2 to 10 carbon atoms.
[0036] (14) In any one of the above (1) to (13) of the present invention, there is provided the resin composition, wherein the content of the acryl copolymer and the compatibilizing portion derived from the acryl copolymer is 0.01 parts by weight to 10 parts by weight relative to 100 parts by weight of the sum of the first biodegradable resin and the second biodegradable resin.
[0037] (15) In any one of the above (1) to (14) of the present invention, there is provided the resin composition, wherein the epoxy equivalent weight (EEW) of the acrylic copolymer is 200 g / eq to 800 g / eq.
[0038] (16) In any one of the above (1) to (15) of the present invention, there is provided the resin composition, wherein the weight average molecular weight of the acrylic copolymer is 10,000 to 100,000.
[0039] (17) In any one of the above (1) to (16) of the present invention, there is provided the resin composition, wherein the acrylic copolymer has a glass transition temperature of 45°C to 85°C.
[0040] (18) The present invention provides a molded product molded from the resin composition according to any one of (1) to (17).
[0041] Beneficial Effects
[0042] The resin composition of the present invention comprises heterogeneous biodegradable resins, wherein the melt index and the number of regions of the dispersed phase are adjusted by improving the compatibility between the heterogeneous biodegradable resins, and thus the resin composition has excellent processability by preventing viscosity increase while improving mechanical properties.
[0043] Furthermore, the molded article of the present invention molded from the resin composition has excellent mechanical properties and exhibits biodegradability. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] Figure 1 This is an image obtained by capturing the resin composition prepared in Example 2 of the present invention at a magnification of 25,000 times using a transmission electron microscope.
[0045] Figure 2 This is an image of the region marked in the transmission electron microscope image of Example 2 of the present invention for counting the number of regions and measuring the region size.
[0046] Figure 3 is an image obtained by capturing an image of the resin composition prepared in Comparative Example 1 of the present invention at a magnification of 25,000 times using a transmission electron microscope.
[0047] Figure 4 This is an image of the region marked in the transmission electron microscope image of Comparative Example 1 of the present invention for counting the number of regions and measuring the region size. DETAILED DESCRIPTION
[0048] Hereinafter, the present invention will be described in more detail to help understanding of the present invention.
[0049] It will be understood that the words or terms used in the specification and claims should not be interpreted as the meanings defined in commonly used dictionaries, and it will also be understood that, based on the principle that the inventor can appropriately define the meanings of words or terms to best explain the present invention, the words or terms should be interpreted as having a meaning consistent with their meanings in the context of the relevant technology and the technical ideas of the present invention.
[0050] As used herein, the term "monomer unit" may refer to a component, structure, or material itself derived from a monomer, and specifically, for example, may refer to a repeating unit formed in a polymer by subjecting an input monomer to a polymerization reaction.
[0051] As used herein, the term "composition" includes not only reaction products and decomposition products formed from the materials of the corresponding composition, but also includes mixtures comprising the materials of the corresponding composition.
[0052] The invention provides a resin composition.
[0053] The resin composition may be a biodegradable resin composition comprising a heterogeneous biodegradable resin. Specifically, for example, the resin composition may include a continuous phase and a dispersed phase, the continuous phase may include a first biodegradable resin, the dispersed phase may include a second biodegradable resin, the melt flow ratio measured at 190°C with a load of 5 kg according to ISO 1133 may be 3.0 g / 10 min to 13.5 g / 10 min, and when an image obtained by performing image capture at a magnification of 25,000 times using a transmission electron microscope (TEM) is observed, the number of regions of the dispersed phase may be 35 or more.
[0054] The resin composition may be in a form in which a dispersed phase formed by including a second biodegradable resin is dispersed in a continuous phase formed by including a first biodegradable resin. The types of the first biodegradable resin and the second biodegradable resin may be different from each other, and any resin referred to as a biodegradable resin may be used. Specifically, for example, the first degradable resin may be a polyester resin containing an aliphatic polyester unit and an aromatic polyester unit. More specifically, for example, the first biodegradable resin may include polybutylene adipate terephthalate (PBAT). PBAT is a random copolymer of adipic acid, 1,4-butanediol and terephthalic acid, and is proposed as an alternative biodegradable resin for low-density polyethylene. In particular, PBAT may ensure the biodegradability of the aliphatic polyester unit formed by adipic acid and 1,4-butanediol, while ensuring the mechanical properties of the aromatic polyester unit formed by terephthalic acid and 1,4-butanediol.
[0055] Any biodegradable resin different from the first biodegradable resin can be used as the second biodegradable resin, and the second biodegradable resin can include, for example, polylactic acid (PLA). PLA corresponds to an eco-friendly biodegradable resin produced from biomaterials and naturally decomposed into water and carbon dioxide within a few months by the action of microorganisms.
[0056] The content of the first biodegradable resin in the resin composition may be 50 to 90 parts by weight relative to the sum of 100 parts by weight of the first biodegradable resin and the second biodegradable resin. For example, relative to the sum of 100 parts by weight of the first biodegradable resin and the second biodegradable resin, the content of the first biodegradable resin in the resin composition may be 50 parts by weight or more, 55 parts by weight or more, 60 parts by weight or more, 65 parts by weight or more, or 70 parts by weight or more, and may be 90 parts by weight or less, 85 parts by weight or less, or 80 parts by weight or less. Within this range, mechanical properties and processability may be more excellent.
[0057] Relative to the sum of 100 parts by weight of the first biodegradable resin and the second biodegradable resin, the content of the second biodegradable resin in the resin composition can be 10 parts by weight to 50 parts by weight. For example, relative to the sum of 100 parts by weight of the first biodegradable resin and the second biodegradable resin, the content of the second biodegradable resin in the resin composition can be more than 10 parts by weight, more than 15 parts by weight, or more than 20 parts by weight, and can be less than 50 parts by weight, less than 45 parts by weight, less than 40 parts by weight, less than 35 parts by weight, or less than 30 parts by weight. Within this range, mechanical properties and processability may be more excellent.
[0058] The melt flow ratio of the resin composition measured at 190°C with a load of 5kg according to ISO 1133 is 3.0g / 10min to 13.5g / 10min. The melt flow ratio indicates viscosity, which is one of the indicators indicating the compatibility between heterogeneous biodegradable resins, and when the viscosity of the resin composition increases, the melt flow ratio decreases. That is, a low melt flow ratio indicates high viscosity. When the melt flow ratio is low, the viscosity increases, and thus the processability may decrease. As described below, the epoxy group of the acryl-based copolymer may react with the carboxylic acid group of polybutylene adipate terephthalate and / or polylactic acid. In this case, when the reaction occurs at the interface between polybutylene adipate terephthalate and / or polylactic acid, a polymerized form of a graft polymer such as polybutylene adipate terephthalate-g-polylactic acid (PBAT-g-PLA) is formed, thereby improving the compatibility between polybutylene adipate terephthalate and polylactic acid by enhancing interfacial adhesion. That is, when the melt flow ratio falls within the range defined in the present invention, this indicates that a graft polymer such as polybutylene adipate terephthalate-g-polylactic acid (PBAT-g-PLA) is formed within an appropriate range. Specifically, for example, according to ISO The melt flow ratio of the resin composition measured at 190° C. with a load of 5 kg may be 3.0 g / 10 min or more, 3.5 g / 10 min or more, 4.0 g / 10 min or more, 4.5 g / 10 min or more, or 4.8 g / 10 min or more, and may be 13.5 g / 10 min or less, 13.4 g / 10 min or less, 13.3 g / 10 min or less, 13.2 g / 10 min or less, 13.1 g / 10 min or less, 13.0 g / 10 min or less, In some embodiments, the present invention relates to a biodegradable resin having a molecular weight of 1 g / 10 min or less, 12.9 g / 10 min or less, 12.8 g / 10 min or less, 12.7 g / 10 min or less, 12.6 g / 10 min or less, 12.5 g / 10 min or less, 12.4 g / 10 min or less, 12.3 g / 10 min or less, 12.2 g / 10 min or less, 12.1 g / 10 min or less, 12.0 g / 10 min or less, 11.9 g / 10 min or less, 11.8 g / 10 min or less, or 11.7 g / 10 min or less. Within this range, the compatibility between the heterogeneous biodegradable resins is improved, so the resin combination has more excellent processability by preventing viscosity from increasing while having improved mechanical properties.
[0059] When observing an image obtained by performing image capture using a transmission electron microscope (TEM) at a magnification of 25000 times, the number of regions of the dispersed phase of the resin composition can be 35 or more. When observing the resin composition using a transmission electron microscope, the dispersed phase containing the second biodegradable resin forms a region in the continuous phase containing the first biodegradable resin. In this case, the number of regions of the dispersed phase dispersed in the same continuous phase varies according to the compatibility of the first biodegradable resin and the second biodegradable resin. That is, due to the excellent compatibility between the first biodegradable resin and the second biodegradable resin, the number of regions of the dispersed phase dispersed in the same continuous phase increases. Specifically, for example, in a resin composition, when observing an image obtained by performing image capture using a transmission electron microscope (TEM) at a magnification of 25000 times, the number of regions of the dispersed phase can be 35 or more, 40 or more, 45 or more, 50 or more, 55 or more, 60 or more, 65 or more, 70 or more, 75 or more, 80 or more, 85 or more, 90 or more, 95 or more, or 100 or more. The upper limit is not specifically limited, but can be less than 1000, less than 900, less than 800, less than 700, less than 600, less than 500, less than 400, less than 300, less than 200 or less than 150. Within this range, the compatibility between heterogeneous biodegradable resins is improved, so the resin composition has more excellent processability by preventing viscosity increase while improving mechanical properties. Here, the image obtained by performing image capture using a transmission electron microscope (TEM) at a magnification of 25000 times can be an image with a size of 3.4 μm (minor axis) and 4.9 μm (major axis) in width. In addition, when counting the number of regions in the image obtained by performing image capture using a transmission electron microscope (TEM) at a magnification of 25000 times, the region to be counted can be a region in which the major diameter in the transmission electron micrograph is more than 150 nm and the lightness is more than 9, wherein the lightness is divided into black as 0, and white as 10. The region size is the arithmetic mean of the size relative to the major axis of each region. For example, the region can be polylactic acid, and the matrix as the continuous phase can be polybutylene adipate terephthalate. The properties of the region can be inferred by the difference in glass transition temperature and melt viscosity between polylactic acid and polybutylene adipate terephthalate. For example, more specifically, since the glass transition temperature of polybutylene adipate terephthalate is low temperature (about -30°C) and the glass transition temperature of polylactic acid is high temperature (about 60°C), the region can have morphological properties exhibited due to the obvious difference in fluidity of the two resins under the same processing conditions.In addition, since polylactic acid as a dispersed phase observed in an image obtained by a transmission electron microscope was confirmed to be bright in color, it is presumed that the effect of transmitting the light beam is stronger than that of polybutylene adipate terephthalate resin.
[0060] When observing an image obtained by image capture using a transmission electron microscope (TEM) at a magnification of 25000 times, the area size of the dispersed phase can be less than 700nm. The area size of the dispersed phase dispersed in the same continuous phase varies according to the compatibility of the first biodegradable resin and the second biodegradable resin. That is, the more excellent the compatibility of the first biodegradable resin and the second biodegradable resin, the smaller the area size of the dispersed phase dispersed in the same continuous phase. For example, when observing an image obtained by image capture using a transmission electron microscope (TEM) at a magnification of 25000 times, the area size of the resin composition can be less than 700nm, less than 650nm, less than 500nm, less than 450nm, or less than 400nm. The lower limit of the area size is not particularly limited, but can be more than 10nm, more than 50nm, more than 100nm, more than 150nm, or more than 200nm. In this range, the compatibility between heterogeneous biodegradable resins is improved, so resin combination has excellent processability by preventing viscosity increase while having mechanical properties. Here, the selection criteria of image size and region are the same as described above. This can show that the area size of each major axis of the region relative to the dispersed phase observed in the image obtained by performing image capture under 25000 times of magnification using a transmission electron microscope (TEM) falls into the above range, or the arithmetic mean of area size falls into the above range.
[0061] The melting enthalpy (ΔHm) of the resin composition is 0.01 J / g to 3.6 J / g, and the melting enthalpy is measured using a differential scanning calorimeter (DSC) in the following manner: adding 8 mg (error range of 1 mg) of sample, heating to 180°C at a heating rate of 10°C / min under a nitrogen flow, then cooling to -50°C at a cooling rate of 10°C / min, and heating to 180°C at a heating rate of 10°C / min. In addition to the melt flow ratio, the melting enthalpy (ΔHm) is also an indicator of the compatibility between heterogeneous biodegradable resins, and specifically, for example, can represent the melting enthalpy (ΔHm) formed during the cold crystallization process of the second biodegradable resin, and more specifically, for example, can represent the melting enthalpy (ΔHm) formed during the cold crystallization process of polylactic acid. When resin combination includes heterogeneous biodegradable resin, the crystallinity of the second biodegradable resin is reduced due to the compatibility between them, and therefore shows the reduction of cold crystallization peak and the reduction of melting enthalpy. Therefore, melting enthalpy (Δ Hm) is measured relative to cold crystallinity, and cold crystallinity changes according to the compatibility between the heterogeneous biodegradable resins in resin combination. Lower melting enthalpy (Δ Hm) shows the excellent compatibility between the heterogeneous biodegradable resins of resin combination. Specifically, for example, the melting enthalpy (ΔHm) of the resin composition can be 0.01 J / g or more, 0.02 J / g or more, 0.03 J / g or more, 0.04 J / g or more, 0.05 J / g or more, 0.06 J / g or more, 0.07 J / g or more, 0.08 J / g or more, 0.09 J / g or more, or 0.1 J / g or more, and can be 3.6 J / g or less, or 3.5 J / g or less, and the melting enthalpy is measured using a differential scanning calorimeter (DSC) in the following manner: adding 8 mg (error range of 1 mg) of the sample, heating once to 180°C at a heating rate of 10°C / min under a nitrogen flow, then cooling to -50°C at a cooling rate of 10°C / min, and heating twice to 180°C at a heating rate of 10°C / min. Within this range, compatibility between heterogeneous biodegradable resins is improved, and thus the resin composition has more excellent processability by preventing viscosity increase while having improved mechanical properties.
[0062] In the resin composition, the weight average molecular weight of the whole resin composition can be 137000 to 200000. Specifically for example, the weight average molecular weight of the whole resin composition can be more than 137000, more than 137500 or more than 138000, and can be less than 200000, less than 195000, less than 190000, less than 185000, less than 180000, less than 175000, less than 170000, less than 165000, less than 160000 or less than 159000. Within this range, in heterogeneous biodegradable resins, particularly in polybutylene adipate terephthalate and / or polylactic acid, graft polymers such as polybutylene adipate terephthalate-g-polylactic acid (PBAT-g-PLA) are formed at an appropriate level, so even if the molecular weight increases, the tensile strength of the resin composition can be further improved. The weight average molecular weight may be expressed without units, but may also be expressed based on molar mass in units of g / mol.
[0063] The tensile strength of the resin composition measured at a tensile speed of 50 mm / min according to ASTM D638 was 245 kgf / cm 2 Up to 500kgf / cm 2 For example, the tensile strength of the resin composition measured according to ASTM D638 may be 245 kgf / cm 2 Above, 250kgf / cm 2 Above, 255kgf / cm 2 Above, or 260kgf / cm 2 Above, and can be 500kgf / cm 2 Below, 490kgf / cm 2 Below, 480kgf / cm 2 Below, 470kgf / cm 2 Below, 460kgf / cm 2 Below, 450kgf / cm 2 Below, 440kgf / cm 2 Below, 430kgf / cm 2 Below, 420kgf / cm 2 Below, or 415kgf / cm 2 the following.
[0064] The elongation of the resin composition measured according to ASTM D638 may be 400% or more. Specifically, for example, the elongation of the resin composition measured according to ASTM D638 may be 400% or more, 410% or more, 420% or more, 430% or more, 440% or more, 450% or more, 460% or more, 470% or more, 480% or more, 490% or more, 500% or more, 510% or more, 520% or more, 530% or more, 540% or more, 550% or more, 560% or more, 570% or more, 580% or more, or 590% or more, and may be 700% or less, 690% or less, 680% or less, 670% or less, or 665% or less.
[0065] The resin composition may further include at least one of an acryl-based copolymer and a compatibilizing portion formed of the acryl-based copolymer.
[0066] The acryl copolymer may be a copolymer containing reactive functional groups such as epoxy groups, and thus may be included as a chemical compatibilizer to improve the compatibility of PBAT and PLA in the resin composition. The acryl copolymer may be present in the resin composition as it is, or may be present in the form of a compatibilized portion through chemical bonding via a reaction of the reactive functional group with the first biodegradable resin and the second biodegradable resin, or the two forms may coexist.
[0067] The acryl copolymer may be an acryl copolymer obtained by copolymerizing a methyl (meth)acrylate monomer, a (meth)acrylate monomer containing an epoxy group, and an alkyl (meth)acrylate monomer having 2 to 10 carbon atoms. For example, the acryl copolymer may be a random copolymer or a linear random copolymer obtained by copolymerizing a methyl (meth)acrylate monomer, a (meth)acrylate monomer containing an epoxy group, and an alkyl (meth)acrylate monomer having 2 to 10 carbon atoms. In this article, "(meth)acrylate" is intended to include both acrylate and methacrylate.
[0068] The acryl copolymer may include 25% to 65% by weight of (meth) methyl acrylate monomer units. Specifically, for example, the content of the (meth) methyl acrylate monomer units formed by the (meth) methyl acrylate monomer in the acryl copolymer may be 25% by weight or more, 30% by weight or more, 35% by weight or more, or 40% by weight or more, and may be 65% by weight or less, 60% by weight or less, 55% by weight or less, or 50% by weight or less. Within this range, the acryl copolymer may have excellent miscibility with the second biodegradable resin and relatively good compatibility with the first biodegradable resin, and thus may further improve the compatibility between the first biodegradable resin and the second biodegradable resin.
[0069] Acryl copolymer can include 15 wt % to 60 wt % of (meth) acrylate monomer units containing epoxy groups formed by (meth) acrylate monomers containing epoxy groups. Specifically for example, the content of (meth) acrylate monomer units containing epoxy groups formed by (meth) acrylate monomers containing epoxy groups in acryl copolymer can be more than 15 wt %, more than 20 wt %, more than 25 wt %, more than 30 wt %, more than 35 wt % or more than 40 wt %, and can be less than 60 wt %, less than 55 wt %, less than 50 wt % or less than 45 wt %. Within this range, the flexibility of polymer chains can be increased, the compatibility between the first biodegradable resin and the second biodegradable resin can be further improved, and in particular, when a film is prepared by a resin combination, chain diffusion and entanglement at the interface between the films can be increased.
[0070] The (meth) acrylate monomer containing an epoxy group may be a (meth) acrylate monomer containing a glycidyl group, and specifically, for example, may be a (meth) glycidyl acrylate monomer. In the (meth) acrylate monomer containing an epoxy group, the epoxy group contained in the monomer may react with the hydroxyl group (-OH) or carboxylic acid group (-COOH) contained in the first biodegradable resin or the second biodegradable resin, and thus may be given a function as a chemical compatibilizer. In addition, when a reaction occurs at the interface between the first biodegradable resin and the second biodegradable resin, the compatibility and interfacial adhesion between the first biodegradable resin and the second biodegradable resin may be further improved.
[0071] Acryl copolymer can include 5 wt % to 32 wt % of (meth) alkyl acrylate monomer units with 2 to 10 carbon atoms formed by (meth) alkyl acrylate monomers with 2 to 10 carbon atoms. Specifically for example, the content of (meth) alkyl acrylate monomer units with 2 to 10 carbon atoms formed by (meth) alkyl acrylate monomers with 2 to 10 carbon atoms in the acryl copolymer can be more than 5 wt %, more than 10 wt % or more than 15 wt %, and content can be less than 32 wt %, less than 31 wt %, less than 30 wt %, less than 25 wt % or less than 20 wt %. Within this range, the flexibility of the polymer chain can be increased, the compatibility between the first biodegradable resin and the second biodegradable resin can be further improved, and in particular, when the film is prepared by the resin combination, the chain diffusion and entanglement at the interface between the films can be increased.
[0072] The (meth)acrylic acid alkyl ester monomer having 2 to 10 carbon atoms may be at least one selected from the group consisting of ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, pentyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, octyl (meth)acrylate, isooctyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, decyl (meth)acrylate, isodecyl (meth)acrylate, dodecyl (meth)acrylate, isobornyl (meth)acrylate, and lauryl (meth)acrylate. For example, the (meth)acrylic acid alkyl ester monomer having 2 to 10 carbon atoms may be an (meth)acrylic acid alkyl ester monomer having 3 to 9 or 4 to 8 carbon atoms, and more specifically, for example, may be at least one selected from the group consisting of butyl (meth)acrylate and 2-ethylhexyl (meth)acrylate.
[0073] The acrylic copolymer may be prepared by emulsion polymerization of a polymerization composition including a polymerization initiator, an emulsifier, and a monomer mixture containing a methyl (meth)acrylate monomer, a (meth)acrylate monomer containing an epoxy group, and an alkyl (meth)acrylate monomer having 2 to 10 carbon atoms.
[0074] In the polymerization process of the acryl-based copolymer, the polymerization may be performed at different polymerization temperatures for different polymerization times as required, and specifically, for example, the polymerization may be performed at a polymerization temperature range of 50° C. to 200° C. for 0.5 to 20 hours.
[0075] The polymerization initiator may be an inorganic or organic peroxide, and specifically, for example, may be a water-soluble polymerization initiator including potassium persulfate, sodium persulfate, ammonium persulfate, and the like, and an oil-soluble polymerization initiator including cumene hydroperoxide, benzoyl peroxide, and the like.
[0076] An activator may be used together with the polymerization initiator to promote triggering of the reaction of the peroxide, and at least one selected from the group consisting of sodium formaldehyde sulfoxylate, sodium ethylenediaminetetraacetate, ferrous sulfate, and dextrose may be used as the activator.
[0077] The polymerization initiator may be added in an amount of 0.1 to 10 parts by weight, and specifically, for example, in an amount of 0.1 to 5 parts by weight, relative to 100 parts by weight of the dry weight of the monomer mixture.
[0078] In terms of improving the efficiency of the polymerization reaction, polymerization can be carried out by further comprising a chain transfer agent. Chain transfer agent can play the role of introducing homopolymer (polymer consisting of only one monomer) into micelle during polymerization. Chain transfer agent can be a straight chain or branched alkyl mercaptan compound with 5 to 20 carbon atoms, and specifically for example, can be hexanethiol, cyclohexanethiol, adamantanethiol, heptylthiol, octylthiol, nonylthiol, decyl mercaptan, undecyl mercaptan, dodecanethiol, hexadecyl mercaptan, octadecyl mercaptan, etc. In addition, relative to the monomer mixture of 100 weight parts, in terms of dry weight, the chain transfer agent addition can be 0.1 weight part to 10 weight parts, and specifically for example, the addition can be 0.1 weight part to 5 weight parts.
[0079] The emulsion polymerization may be performed by including steps (S10) to (S30).
[0080] (S10) Step: preparing an emulsion by dispersing an emulsifier in a solvent.
[0081] (S20) Step: Preparing a pre-emulsion by mixing a monomer mixture containing a monomer component and an emulsifier and the like.
[0082] Step (S30): The emulsion prepared in step (S10) and the pre-emulsion prepared in step (S20) are mixed, and emulsion polymerization is performed in the presence of a polymerization initiator.
[0083] The emulsion polymerization for polymerizing the acrylic-based copolymer may be performed according to steps (S10) to (S30).
[0084] First, in step (S10), an emulsion containing an emulsifier is prepared. This step is a step separated from the following pre-emulsion preparation process. As an emulsifier, an anionic emulsifier can be used alone, or an anionic emulsifier, a cationic emulsifier and a nonionic emulsifier can be used together, and the emulsion can be prepared by mixing the emulsifier component with a solvent such as water. In the preparation process of the emulsion, initial micelle particles of several nanometers in size can be stably formed. Step (S20) is a preparation step of a pre-emulsion containing a monomer mixture, in which the pre-emulsion is prepared by mixing the above-mentioned monomers, emulsifiers, etc. with water. In this case, as an emulsifier, an anionic emulsifier can also be used alone, or an anionic emulsifier and a nonionic emulsifier can be used together. In this process, nano-sized latex particles can be formed in the pre-emulsion. That is, the above-mentioned emulsifier can be used in the emulsifier preparation step and / or the pre-emulsion preparation step. In step (S30), after the polymerization initiator is added to the emulsion thus prepared, the pre-emulsion and the polymerization initiator are continuously added in equal proportions for a predetermined time.
[0085] Relative to 100 parts by weight of the monomer mixture, the amount of the polymerization initiator put into the emulsion can be greater than 0 parts by weight and equal to or less than 1 part by weight, and the amount of the polymerization initiator put in with the pre-emulsion can be 0.1 parts by weight to 2 parts by weight relative to 100 parts by weight of the monomer mixture, and the continuous input time can be about 3 hours to about 7 hours. Through this process, the monomer or polymer suspended in the pre-emulsion can be put into the initial particles formed in the emulsion. The product of the reaction can then undergo a thermal polymerization process in the presence of another polymerization initiator, and through this process, the residual monomer is polymerized. In this case, relative to 100 parts by weight of the monomer mixture, 0.1 parts by weight to 10 parts by weight of the polymerization initiator can be further put in, and the thermal polymerization can be carried out at a temperature of about 75°C to about 85°C for about 40 minutes to about 80 minutes. This emulsion polymerization method is binary into an emulsion preparation process and a pre-emulsion preparation process, and can then be carried out by a simple method of mixing the pre-emulsion with the emulsion, thereby improving process stability and productivity compared to conventional methods.
[0086] The emulsifier used for emulsion polymerization can include at least one selected from the group consisting of anionic emulsifiers, cationic emulsifiers and nonionic emulsifiers. Emulsifiers are materials having both hydrophilic groups and hydrophobic groups, forming micellar structures during emulsion polymerization, and allowing each monomer to polymerize in the micellar structure. Emulsifiers commonly used in emulsion polymerization can be divided into anionic emulsifiers, cationic emulsifiers and nonionic emulsifiers, and in terms of polymerization stability in emulsion polymerization, two or more emulsifiers can be mixed and used. As a specific example, nonionic emulsifiers can include at least one selected from the group consisting of polyethylene glycol alkyl aryl ether, polyethylene glycol alkylamine and polyethylene glycol alkyl ester. In addition, anionic emulsifiers can include at least one selected from the group consisting of alkyl diphenyl ether sodium disulfonate, polyethylene glycol alkyl ether sodium sulfate, polyethylene glycol aryl ether sodium sulfate, alkyl sodium sulfate, alkyl benzene sodium sulfonate and dialkyl sodium sulfosuccinate. These can be used alone or as a mixture of two or more, and can be more effective when used as a mixture of anionic emulsifiers and nonionic emulsifiers. In addition, the amount of the emulsifier can be from about 0.1 parts by weight to about 10 parts by weight, or from about 1 part by weight to about 5 parts by weight, relative to 100 parts by weight of the total monomer components used in the preparation of the latex particles.
[0087] In addition to the emulsifier or the monomer component, the composition for polymerization may further include an aqueous solvent such as water. In this case, in terms of stability of latex particles and viscosity control, the amount of the aqueous solvent may be about 10 parts by weight to 1000 parts by weight relative to 100 parts by weight of the latex particles, and the aqueous solvent may be used so that the total solid content (TSC) is adjusted to about 10% by weight to about 60% by weight relative to the total amount of the composition.
[0088] The acryl-based copolymer and the compatibilizing portion derived from the acryl-based copolymer in the resin composition may be included in an amount of 0.01 to 10.0 parts by weight relative to 100 parts by weight of the total of the first biodegradable resin and the second biodegradable resin. For example, the content of the acryl copolymer and the compatibilized part derived from the acryl copolymer in the resin composition may be 0.01 parts by weight or more, 0.02 parts by weight or more, 0.03 parts by weight or more, 0.04 parts by weight or more, 0.05 parts by weight or more, 0.06 parts by weight or more, 0.07 parts by weight or more, 0.08 parts by weight or more, 0.09 parts by weight or more, or 0.1 parts by weight or more, relative to 100 parts by weight of the total of the first biodegradable resin and the second biodegradable resin, and the content may be 10.0 parts by weight or less, 9.0 parts by weight or less, 8.0 parts by weight or less, 7.0 parts by weight or less, 6.0 parts by weight or less, 5.0 parts by weight or less, 4.5 parts by weight or less, 4.0 parts by weight or less, 3.5 parts by weight or less, 3.0 parts by weight or less, 2.5 parts by weight or less, 2.0 parts by weight or less, 1.5 parts by weight or less, or 1.0 parts by weight or less. Within this range, compatibility between heterogeneous biodegradable resins may be further improved, and thus the resin composition may have more excellent aspect of processability by preventing viscosity increase while having further improved mechanical properties.
[0089] The epoxy equivalent weight (EEW) of the acryl copolymer may be 200 g / eq to 800 g / eq. Specifically, for example, the epoxy equivalent weight (EEW) of the acryl copolymer may be 200 g / eq or more, 210 g / eq or more, 220 g / eq or more, 230 g / eq or more, 240 g / eq or more, 260 g / eq or more, 270 g / eq or more, 280 g / eq or more, 290 g / eq or more, 300 g / eq or more, 310 g / eq or more, 320 g / eq or more, 330 g / eq or more, 340 g / eq or more, or 350 g / eq or more, and may be 800 g / eq or less, or 700 g / eq or less. In some embodiments, the compatibility of the biodegradable resins is less than 600g / eq, less than 500g / eq, less than 490g / eq, less than 480g / eq, less than 470g / eq, less than 460g / eq, less than 450g / eq, less than 440g / eq, less than 430g / eq, less than 420g / eq, less than 410g / eq, less than 400g / eq, less than 390g / eq, less than 380g / eq, less than 370g / eq, or less than 360g / eq. Within this range, the compatibility between the heterogeneous biodegradable resins can be further improved. Especially, when the biodegradable resin is a polyester resin, the reaction with the hydroxyl or carboxylic acid group of the polyester resin is effectively carried out, so the property as a chemical compatibilizer can be further improved.
[0090] The weight average molecular weight of the acryl copolymer can be 10,000 to 100,000. Specifically, for example, the weight average molecular weight of the acryl copolymer can be more than 10,000, more than 15,000, more than 20,000, more than 25,000, or more than 30,000, and the weight average molecular weight can be less than 100,000, less than 90,000, less than 80,000, less than 70,000, less than 60,000, less than 50,000, or less than 40,000. Within this range, without affecting the inherent properties of the heterogeneous biodegradable resin (particularly polyester resin), the role as a chemical compatibilizer can be more excellent. The weight average molecular weight can be expressed in a unitless manner, but can also be expressed in g / mol according to the molar mass.
[0091] The glass transition temperature of the acryl copolymer may be 45°C to 85°C. Specifically, for example, the glass transition temperature of the acryl copolymer may be 45°C or more, 46°C or more, 47°C or more, 48°C or more, 49°C or more, 50°C or more, 51°C or more, 52°C or more, 53°C or more, 54°C or more, 55°C or more, 56°C or more, 57°C or more, 58°C or more, or 59°C or more, and may be 85°C or less, 84°C or less. 83°C or less, 82°C or less, 81°C or less, 80°C or less, 79°C or less, 78°C or less, 77°C or less, 76°C or less, 75°C or less, 74°C or less, 73°C or less, 72°C or less, 71°C or less, or 70°C or less. Within this range, the resin composition containing the heterogeneous biodegradable resin can be more easily processed into a compatibilizer.
[0092] The present invention provides a shaped article.
[0093] The molded article may be a biodegradable molded article molded from a resin composition (ie, a biodegradable resin composition). Herein, the molded article includes a film-molded article formed by film formation, an injection-molded article formed by injection, and the like.
[0094] The shaped article may be a biodegradable film, and specifically, for example, may be an agricultural mulch film or a film used as a food packaging material.
[0095] Hereinafter, the embodiments of the present invention will be described in detail so that those skilled in the art can easily implement the present invention. However, the present invention can be implemented in many different forms and should not be construed as being limited to the embodiments set forth herein.
[0096] Preparation Example and Comparative Preparation Example: Preparation of Acryl Copolymer
[0097] Preparation Example 1
[0098] 200 parts by weight of distilled water and 0.5 parts by weight of sodium dioctylsulfosuccinate (sodium bis(2-ethylhexyl)sulfosuccinate) as an emulsifier were added to a 3 L volume glass reactor equipped with a thermometer, a stirrer, a dropping funnel, a nitrogen inlet tube and a reflux cooler, relative to 100 parts by weight of the total weight of methyl methacrylate, glycidyl methacrylate, butyl acrylate and 2-ethylhexyl acrylate as monomers and stirred. During the stirring, the inside of the reactor was replaced with nitrogen, and then the glass reactor was heated to 70° C. 0.2 parts by weight of potassium persulfate was added and the resulting mixture was stirred for 10 minutes.
[0099] Separately, 45 parts by weight of methyl methacrylate, 40 parts by weight of glycidyl methacrylate, and 15 parts by weight of butyl acrylate as monomers were placed in a beaker and mixed thoroughly for 30 minutes. 0.5 parts by weight of 1-octanethiol as a chain transfer agent was added to the mixture relative to 100 parts by weight of the total monomers, mixed thoroughly with a stirrer, and then the resulting mixture was continuously placed in an equal proportion in a glass reactor for 4 hours.
[0100] Thereafter, after 4 hours of polymerization reaction time, the internal temperature of the glass reactor was maintained at 70° C. for 30 minutes and then cooled to room temperature. The obtained emulsion polymerization product was coagulated using an aqueous solution of calcium acetate, heat-treated to raise its temperature to 85° C., then dehydrated and dried at 60° C. for 16 hours to obtain an acrylic copolymer.
[0101] Preparation Example 2
[0102] An acryl-based copolymer was obtained in the same manner as in Preparation Example 1, except that in Preparation Example 1, 15 parts by weight of 2-ethylhexyl acrylate was added instead of 15 parts by weight of butyl acrylate.
[0103] Preparation Example 3
[0104] An acrylic copolymer was obtained in the same manner as in Preparation Example 1, except that in Preparation Example 1, 55 parts by weight were added instead of 45 parts by weight of methyl methacrylate and 30 parts by weight were added instead of 40 parts by weight of glycidyl methacrylate.
[0105] Preparation Example 4
[0106] An acrylic copolymer was obtained in the same manner as in Preparation Example 1, except that in Preparation Example 1, 30 parts by weight were added instead of 45 parts by weight of methyl methacrylate and 55 parts by weight were added instead of 40 parts by weight of glycidyl methacrylate.
[0107] Preparation Example 5
[0108] An acrylic copolymer was obtained in the same manner as in Preparation Example 1, except that in Preparation Example 1, 30 parts by weight were added instead of 45 parts by weight of methyl methacrylate, 55 parts by weight were added instead of 40 parts by weight of glycidyl methacrylate, and 15 parts by weight of 2-ethylhexyl acrylate were added instead of 15 parts by weight of butyl acrylate.
[0109] Preparation Example 6
[0110] An acrylic copolymer was obtained in the same manner as in Preparation Example 1, except that in Preparation Example 1, 55 parts by weight were used instead of 45 parts by weight of methyl methacrylate, 20 parts by weight were used instead of 40 parts by weight of glycidyl methacrylate, and 25 parts by weight of 2-ethylhexyl acrylate were used instead of 15 parts by weight of butyl acrylate.
[0111] Comparative Preparation Example 1
[0112] A commercially available copolymer (a copolymer of methyl methacrylate, butyl acrylate, glycidyl methacrylate, and styrene) used in the preparation of the master batch A described in Patent Document 1 was used.
[0113] Comparative Preparation Example 2
[0114] An acrylic copolymer was obtained in the same manner as in Preparation Example 1, except that in Preparation Example 1, 64 parts by weight were added instead of 45 parts by weight of methyl methacrylate, 2.1 parts by weight were added instead of 40 parts by weight of glycidyl methacrylate, and 33.9 parts by weight were added instead of 15 parts by weight of butyl acrylate.
[0115] Comparative Preparation Example 3
[0116] An acrylic copolymer was obtained in the same manner as in Preparation Example 1, except that in Preparation Example 1, 62.3 parts by weight were added instead of 45 parts by weight of methyl methacrylate, 5.2 parts by weight were added instead of 40 parts by weight of glycidyl methacrylate, and 32.5 parts by weight of 2-ethylhexyl acrylate was added instead of 15 parts by weight of butyl acrylate.
[0117] Comparative Preparation Example 4
[0118] An acrylic copolymer was obtained in the same manner as in Preparation Example 1, except that in Preparation Example 1, 60 parts by weight were added instead of 45 parts by weight of methyl methacrylate, 10 parts by weight were added instead of 40 parts by weight of glycidyl methacrylate, and 30 parts by weight were added instead of 15 parts by weight of butyl acrylate.
[0119] Examples and Comparative Examples: Preparation of Resin Compositions
[0120] Example 1
[0121] Polybutylene adipate terephthalate (manufacturer: Xinjiang Blue Mountain Tunhe Chemical Co., Ltd., product name: TH801T) and polylactic acid (manufacturer: Natureworks, product name: Ingeo Biopolymer 2003D) were dried in an oven at 60° C. for 24 hours.
[0122] Subsequently, 80 parts by weight of polybutylene adipate terephthalate, 20 parts by weight of polylactic acid, and 0.3 parts by weight of the acryl-based copolymer obtained according to Preparation Example 1 were mixed and blended at 170° C. and 60 rpm for 10 minutes using a Haake rheomix OS laboratory mixer manufactured by Thermo Electron Karlsruhe GmbH Co., Ltd. Thereafter, a resin composition was obtained by grinding the resulting mixture.
[0123] Example 2
[0124] A resin composition was obtained in the same manner as in Example 1, except that 1.0 parts by weight of the acrylic copolymer obtained according to Preparation Example 1 was added instead of 0.3 parts by weight in Example 1.
[0125] Example 3
[0126] A resin composition was obtained in the same manner as in Example 1, except that 1.0 parts by weight of the acryl-based copolymer obtained according to Preparation Example 2 was added, unlike Example 1 in which 0.3 parts by weight of the acryl-based copolymer obtained according to Preparation Example 1 was added.
[0127] Example 4
[0128] A resin composition was obtained in the same manner as in Example 1, except that 1.0 parts by weight of the acryl-based copolymer obtained according to Preparation Example 3 was added, unlike Example 1 in which 0.3 parts by weight of the acryl-based copolymer obtained according to Preparation Example 1 was added.
[0129] Example 5
[0130] A resin composition was obtained in the same manner as in Example 1, except that 1.0 parts by weight of the acryl-based copolymer obtained according to Preparation Example 4 was added, unlike Example 1 in which 0.3 parts by weight of the acryl-based copolymer obtained according to Preparation Example 1 was added.
[0131] Example 6
[0132] A resin composition was obtained in the same manner as in Example 1, except that 1.0 parts by weight of the acryl-based copolymer obtained according to Preparation Example 5 was added, unlike Example 1 in which 0.3 parts by weight of the acryl-based copolymer obtained according to Preparation Example 1 was added.
[0133] Example 7
[0134] A resin composition was obtained in the same manner as in Example 1, except that 1.0 parts by weight of the acryl-based copolymer obtained according to Preparation Example 6 was added, unlike Example 1 in which 0.3 parts by weight of the acryl-based copolymer obtained according to Preparation Example 1 was added.
[0135] Comparative Example 1
[0136] A resin composition was obtained in the same manner as in Example 1, except that the acrylic copolymer obtained according to Preparation Example 1 was not input, which was different from Example 1.
[0137] Comparative Example 2
[0138] A resin composition was obtained in the same manner as in Example 1, except that 1.0 parts by weight of the acryl-based copolymer obtained according to Comparative Preparation Example 1 was input, unlike Example 1 in which 0.3 parts by weight of the acryl-based copolymer obtained according to Preparation Example 1 was input.
[0139] Comparative Example 3
[0140] A resin composition was obtained in the same manner as in Example 1, except that 1.0 parts by weight of the acryl-based copolymer obtained according to Comparative Preparation Example 2 was added, unlike Example 1 in which 0.3 parts by weight of the acryl-based copolymer obtained according to Preparation Example 1 was added.
[0141] Comparative Example 4
[0142] A resin composition was obtained in the same manner as in Example 1, except that 1.0 parts by weight of the acryl-based copolymer obtained according to Comparative Preparation Example 3 was added, unlike Example 1 in which 0.3 parts by weight of the acryl-based copolymer obtained according to Preparation Example 1 was added.
[0143] Comparative Example 5
[0144] A resin composition was obtained in the same manner as in Example 1, except that 1.0 parts by weight of the acryl-based copolymer obtained according to Comparative Preparation Example 4 was added, unlike Example 1 in which 0.3 parts by weight of the acryl-based copolymer obtained according to Preparation Example 1 was added.
[0145] Experimental example
[0146] Experimental Example 1
[0147] The glass transition temperature, molecular weight and epoxy equivalent of each of the acrylic copolymers prepared in Preparation Examples 1 to 6 and Comparative Preparation Examples 2 to 4 were measured by the following methods, and the measurement results are listed in the following Table 1 together with the monomer composition.
[0148] Furthermore, the glass transition temperature, molecular weight, and epoxy equivalent of the copolymer of Comparative Preparation Example 1 were measured, and the measurement results are listed in Table 1 below.
[0149] *Glass transition temperature (°C): The glass transition temperature was measured using a differential scanning calorimeter (manufacturer: TA Instruments, model name: DSC 250) in the following manner: 8 mg (error range 1 mg) of a sample of each acryl-based copolymer prepared in the Preparation Example and the Comparative Preparation Example was input; primary heating to 300°C at a heating rate of 10°C / min under a nitrogen flow; cooling to 0°C at a temperature reduction rate of 10°C / min; and secondary heating to 300°C at a heating rate of 10°C / min.
[0150] *Weight average molecular weight and number average molecular weight: The weight average molecular weight and number average molecular weight of the obtained acrylic copolymer sample were measured under the following conditions using gel permeation chromatography (GPC, PL GPC220, manufactured by Agilent Technologies Co., Ltd.). In this case, a part of a solution having a concentration of 2 mg / ml dissolved in tetrahydrofuran (stabilized with BHT) as a solvent was taken out and used as a sample.
[0151] - Column: PL MiniMixed BX 2
[0152] -Solvent: Tetrahydrofuran (stabilized with BHT)
[0153] -Flow rate: 0.3ml / min
[0154] -Sample concentration: 2.0mg / ml
[0155] - Column temperature: 40℃
[0156] -Detector: Waters 2414 Refractive Index Detector
[0157] -Data processing: empowerment
[0158] -Calibration curve: using polystyrene standards (nine molecular weights: 2000 / 10000 / 30000 / 70000 / 200000 / 700000 / 2000000 / 4000000 / 10000000)
[0159] *Epoxy equivalent (g / eq): The content ratio (molar ratio) of glycidyl methacrylate was measured using a 700 MHz NMR spectrometer manufactured by Bruker Co., Ltd. according to nuclear magnetic resonance spectroscopy, the equivalent number of epoxy groups (eq / mol) was obtained from the measured value, and the epoxy equivalent weight (g / eq) was calculated by using the number average molecular weight (Mn) measured above.
[0160] Table 1
[0161]
[0162] Experimental Example 2
[0163] The melt flow ratio, melting enthalpy (ΔHm), and the number and size of domains of the resin compositions prepared in Examples 1 to 7 and Comparative Examples 1 to 5 were measured in the following manner, and the measurement results are listed in Table 2 below.
[0164] * Melt flow ratio (MFR): The melt flow ratio of the obtained resin composition sample was measured using a melt flow indexer MI-4 manufactured by Gettfert Co., Ltd. according to ISO 1133 (190° C., 5 kg).
[0165] * Melting enthalpy (ΔHm): The melting enthalpy (ΔHm) was measured using a differential scanning calorimeter (DSC) in the following manner: 8 mg (error range 1 mg) of a sample of each acryl copolymer prepared in the Preparation Example and the Comparative Preparation Example was added; the mixture was heated to 180°C at a heating rate of 10°C / min under a nitrogen flow; the mixture was then cooled to -50°C at a temperature decreasing rate of 10°C / min; and the mixture was heated to 180°C at a heating rate of 10°C / min for a second time.
[0166] *The number and size of regions: The number and size of regions were measured by: preparing thin sections using a microtome; preparing a specimen by staining with osmium tetroxide vapor; capturing a specimen image at a magnification of 25,000 times using a transmission electron microscope; and counting the number of regions and measuring the size of the regions by using Image J software. In this case, when counting the number of regions and measuring the size of the regions, the regions to be counted are regions exhibiting a lightness of 9 or more selected from regions having a long diameter of 150 nm or more in the transmission electron micrograph, where the lightness is divided into black as 0 and white as 10. The region size is the arithmetic mean of the size relative to the long axis of each region.
[0167] The images obtained by capturing the resin compositions according to Example 2 and Comparative Example 1 at a magnification of 25,000 times using a transmission electron microscope are respectively Figure 1 (Example 2) and Figure 3 (Comparative Example 1) and the images showing the areas marked for counting the number of areas and measuring the area size are shown in Figure 2 (Example 2) and Figure 4 (Comparative Example 1) is shown.
[0168] Table 2
[0169]
[0170] As shown in Table 2, it can be seen that the melt flow ratio of the resin composition prepared according to Examples 1 to 7 of the present invention exhibits a value of 3.0 g / 10min to 13.5 g / 10min, the melting enthalpy exhibits a value of 0.01 J / g to 3.6 J / g, the number of regions is more than 50, and the region size is less than 650 nm.
[0171] Meanwhile, it can be seen that the melt flow ratio of the resin compositions prepared in Comparative Examples 1 and 3 to 5 is higher than 13.5 g / 10 min, the melting enthalpy is also higher than 3.6 J / g, the number of domains is 19 to 24, and the domain size is 700 nm or more.
[0172] In particular, it can be seen that the melting enthalpy of the resin composition prepared in Comparative Example 2 containing the copolymer prepared in Comparative Preparation Example 1 is so low that the melt flow ratio does not appear due to a rapid increase in viscosity.
[0173] Experimental Example 3
[0174] The molecular weight, molecular weight distribution, tensile strength and elongation of the resin compositions prepared in Examples 1 to 7 and Comparative Examples 1 to 5 were measured in the following manner, and the measurement results are listed in Table 3 below.
[0175] *Weight average molecular weight and molecular weight increase rate: The weight average molecular weight of the obtained resin composition sample was measured under the following conditions using gel permeation chromatography (GPC, PL GPC220, manufactured by Agilent Technologies Co., Ltd.) In this case, a part of a solution having a concentration of 1 mg / ml obtained by dissolving in chloroform as a solvent was taken out and used as a sample.
[0176] - Column: PL MiniMixed BX 2
[0177] -Solvent: Chloroform
[0178] -Flow rate: 1.0ml / min
[0179] -Sample concentration: 1.0mg / ml
[0180] - Column temperature: 40℃
[0181] -Detector: Waters 2414 Refractive Index Detector
[0182] -Data processing: empowerment
[0183] -Calibration curve: using polystyrene standards (nine molecular weights: 2000 / 10000 / 30000 / 70000 / 200000 / 700000 / 2000000 / 4000000 / 10000000)
[0184] Furthermore, the increase rates of the weight average molecular weights measured for the resin compositions of Examples 1 to 7 and Comparative Examples 2 to 5 relative to the weight average molecular weight measured for the resin composition of Comparative Example 1 without adding the acrylic copolymer were calculated according to the following Equation 1, and the calculation results are listed.
[0185] [Equation 1]
[0186] Molecular weight increase rate = (weight average molecular weight measured for the resin compositions of Examples 1 to 7 and Comparative Examples 2 to 5 / weight average molecular weight measured for the resin composition of Comparative Example 1) × 100
[0187] *Tensile strength and elongation: The obtained resin compositions were each placed in a mold having a size of 130 mm×130 mm×2 mm, preheated at 180° C. for about 5 minutes, and then compression-processed under a compressive load of 20 MPa for 3 minutes, and then quenched at room temperature to prepare a sample. The prepared test specimens were made into test specimens according to ASTM D638 and Type 4 standards, and the elongation and tensile strength were measured using a general physical property tester (Instron 3365) manufactured by Instron Co., Ltd. under the condition of 50 mm / min according to ASTM D638 standards.
[0188] Table 3
[0189]
[0190] As shown in Tables 2 and 3 above, it can be confirmed that the resin compositions prepared in Examples 1 to 7 whose melt flow ratio and the number of regions fall within the range defined in the present invention have more excellent tensile strength while maintaining an elongation equal to or greater than the elongation of the resin compositions of Comparative Examples 1 and 3 to 5 whose melt flow ratio and the number of regions are outside the range defined in the present invention.
[0191] On the other hand, it can be confirmed that the resin composition of Comparative Example 2 containing the copolymer disclosed in Patent Document 1 as a compatibilizer has a significantly increased weight average molecular weight and thus exhibits increased tensile strength compared to the resin composition prepared in Comparative Example 1 without a compatibilizer, but the elongation is rapidly reduced compared to the resin compositions of Examples 1 to 7 containing the same amount of the acryl-based copolymer. This is expected to be due to the fact that the copolymer as a compatibilizer in the resin composition of Comparative Example 2 not only forms PBAT-g-PLA due to the high reactivity of the copolymer, but also acts as a chain extender for each resin to form a large amount of PBAT-g-PBAT and / or PLA-g-PLA, thereby rapidly increasing the molecular weight.
[0192] It can also be seen that the weight average molecular weight of the resin compositions of Examples 1 to 7 increases compared to Comparative Example 1. This is due to the fact that the acryl-based copolymer as a compatibilizer induces chemical bonding at the interface between polybutylene adipate terephthalate and polylactic acid, thereby functioning as a chain extender.
[0193] On the other hand, it can be seen that the weight average molecular weight of the resin compositions of Comparative Examples 3 to 5 is not increased, or is slightly increased, compared with Example 1. This indicates that even if an acrylic copolymer is used as a compatibilizer, when the melt flow ratio and the number of domains of the resin composition cannot be adjusted within the range defined in the present invention, the effect of increasing the molecular weight does not occur.
[0194] From these results, it can be seen that the compatibility between heterogeneous biodegradable resins is improved, and thus the resin composition has excellent processability by preventing viscosity increase while having improved mechanical properties.
Claims
1. A resin composition comprising a continuous phase and a dispersed phase, in, The continuous phase comprises a first biodegradable resin, The dispersed phase comprises a second biodegradable resin, The melt flow ratio measured at 190°C with a load of 5 kg according to ISO 1133 is 3.0 g / 10 min to 13.5 g / 10 min, and When an image obtained by performing image capturing at a magnification of 25,000 times using a transmission electron microscope (TEM) is observed, the number of domains of the dispersed phase is 35 or more.
2. The resin composition according to claim 1, wherein The first biodegradable resin comprises an aliphatic polyester unit and an aromatic polyester unit.
3. The resin composition according to claim 1, wherein The first biodegradable resin includes polybutylene adipate terephthalate.
4. The resin composition according to claim 1, wherein The second biodegradable resin includes polylactic acid.
5. The resin composition according to claim 1, wherein The first biodegradable resin is contained in an amount of 50 to 90 parts by weight, and the second biodegradable resin is contained in an amount of 10 to 50 parts by weight, relative to 100 parts by weight of the total of the first and second biodegradable resins.
6. The resin composition according to claim 1, wherein The resin composition has a melt flow ratio measured at 190° C. with a load of 5 kg according to ISO 1133 of 4.5 to 12.0 g / 10 min.
7. The resin composition according to claim 1, wherein The domain size of the dispersed phase observed in an image obtained by performing image capture at a magnification of 25,000 times using a transmission electron microscope (TEM) was 700 nm or less.
8. The resin composition according to claim 1, wherein The melting enthalpy (ΔHm) is 0.01 J / g to 3.6 J / g, and the melting enthalpy is measured using a differential scanning calorimeter (DSC) in the following manner: 8 mg of sample is added with an error range of 1 mg, and heated to 180°C at a heating rate of 10°C / min under a nitrogen flow, and then cooled to -50°C at a cooling rate of 10°C / min, and heated to 180°C at a heating rate of 10°C / min for a second time.
9. The resin composition according to claim 1, wherein The weight average molecular weight of the entire resin composition is 137,000 to 200,000.
10. The resin composition according to claim 1, wherein The tensile strength of the resin composition measured at a tensile speed of 50 mm / min according to ASTM D638 is 245 kgf / cm 2 Up to 500kgf / cm 2 . 11 . The resin composition according to claim 1 , further comprising at least one of an acrylic copolymer and a compatibilizing portion derived from the acrylic copolymer.
12. The resin composition according to claim 11, wherein The acryl-based copolymer includes a methyl (meth)acrylate monomer unit, a (meth)acrylate monomer unit containing an epoxy group, and an alkyl (meth)acrylate-based monomer unit having 2 to 10 carbon atoms.
13. The resin composition according to claim 11, wherein The acryl-based copolymer includes 25 to 65 wt % of methyl (meth)acrylate monomer units, 15 to 60 wt % of (meth)acrylate monomer units containing epoxy groups, and 5 to 32 wt % of alkyl (meth)acrylate monomer units having 2 to 10 carbon atoms.
14. The resin composition according to claim 11, wherein The content of the acryl-based copolymer and the compatibilizing portion derived from the acryl-based copolymer is 0.01 parts by weight to 10 parts by weight relative to 100 parts by weight of the total of the first biodegradable resin and the second biodegradable resin.
15. The resin composition according to claim 11, wherein The epoxy equivalent weight (EEW) of the acrylic copolymer is 200 g / eq to 800 g / eq.
16. The resin composition according to claim 11, wherein The weight average molecular weight of the acrylic copolymer is 10,000 to 100,000.
17. The resin composition according to claim 11, wherein The acrylic copolymer has a glass transition temperature of 45° C. to 85° C.
18. A molded product molded from the resin composition according to any one of claims 1 to 17.
